An Analysis on Students' Pronunciation for Speaking Presentation of Tourism Industry at SMK 1 Gowa - Azisyah, Siti Nurul; Sulfasyah; Hijrah (FKIP Unismuh Makassar, 2023)
The purpose of this study was to find out how the pronunciation of students majoring in tourism when making English presentations and what factors influenced their presentations. This research is descriptive quantitative. The subjects of this study were students of class XI UPW 1 SMK 1 Gowa with a total of 29 students. The research instrument used was using questionnaires and interviews. The results showed that students' English pronunciation was still not good enough and it was influenced by internal and external factors experienced by students when they made presentations. There are several internal factors that greatly affect the quality of students’ presentation. These include: students’ motivation in learning English, students’ interesting, students’ mood, nervous, unconfident, and memory ability. In addition, external factors that have the potential to be experienced by students during presentations include the students’ social environment, the class condition, inadequate media, poor learning methods, incomplete facilities, lack of practice.